2021
DOI: 10.1055/a-1520-4784
|View full text |Cite
|
Sign up to set email alerts
|

An Oppositional Tolerance Account for Potential Cognitive Deficits Caused by the Discontinuation of Antidepressant Drugs

Abstract: Depression is the leading cause of disability worldwide, making antidepressant drugs the most used psychiatric drugs in the USA. Withdrawal effects and rebound symptoms frequently occur after the reduction and/or discontinuation of these drugs. Although these phenomena have been investigated with respect to the clinical symptomatology, no studies have systematically investigated the effects of withdrawal/rebound on general cognition. We present a novel framework based on the idea of allostatic adaptation, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…98 Further, given that atVNS has been approved for the treatment of pharmacoresistant depression, 43 it might be better suited for OUD than standard pharmacotherapy such as antidepressants, which are often accompanied by side-effects or withdrawal and rebound phenomena when discontinued. 99 More importantly, a systemic review revealed that MMT does not only show a very limited effectivity, but even detrimental effects in restoring normal cognitive control functioning, which is crucial to regain control over opioid intake. 9 Indeed MMT patients, compared to abstinent heroin users or non-user healthy controls, displayed reduced psychomotor speed and impairments in working memory, planning and response inhibition.…”
Section: Atvns As Adjuvant Treatment To Mmt?mentioning
confidence: 99%
See 1 more Smart Citation
“…98 Further, given that atVNS has been approved for the treatment of pharmacoresistant depression, 43 it might be better suited for OUD than standard pharmacotherapy such as antidepressants, which are often accompanied by side-effects or withdrawal and rebound phenomena when discontinued. 99 More importantly, a systemic review revealed that MMT does not only show a very limited effectivity, but even detrimental effects in restoring normal cognitive control functioning, which is crucial to regain control over opioid intake. 9 Indeed MMT patients, compared to abstinent heroin users or non-user healthy controls, displayed reduced psychomotor speed and impairments in working memory, planning and response inhibition.…”
Section: Atvns As Adjuvant Treatment To Mmt?mentioning
confidence: 99%
“…Indeed, mixing benzodiazepine, a drug prescribed to treat opiate withdrawal symptoms, with MMT can be lethal because of respiratory depression 98 . Further, given that atVNS has been approved for the treatment of pharmacoresistant depression, 43 it might be better suited for OUD than standard pharmacotherapy such as antidepressants, which are often accompanied by side‐effects or withdrawal and rebound phenomena when discontinued 99 . More importantly, a systemic review revealed that MMT does not only show a very limited effectivity, but even detrimental effects in restoring normal cognitive control functioning, which is crucial to regain control over opioid intake 9 .…”
Section: Atvns As Adjuvant Treatment To Mmt?mentioning
confidence: 99%